ABSOLUTE AND COMPARATIVE SUSTAINABILITY OF FARMING ENTERPRISES IN BULGARIA - H. Bachev (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
Evaluating absolute and comparative sustainability of farming enterprises is among the most topical issues for researchers, farmers, investors, administrators, politicians, interests groups and public at large. Nevertheless, in Bulgaria and most East European countries there are no comprehensive assessments on sustainability level of Bulgarian farms of different juridical type. This article applies a holistic framework and assesses absolute and comparative sustainability major farming structures in Bulgaria - unregistered farms of Natural Persons, Sole Traders, Cooperatives, and Companies. First, method of the study is outlined, and overall characteristics of surveyed farming enterprises presented. After that an assessment is made of integral, governance, economic, social, environmental sustainability of farming structures of different juridical type. Next, structure of farming enterprises with different sustainability levels is analyzed. Finally, conclusion from the study and directions for further research and amelioration of sustainability assessments suggested.